Core-shell nanocomposites prepared by hierarchical co-assembly: the role of the carbon shell in catalytic wet peroxide oxidation processes - Ribeiro, Rui (2016)
The diffraction pattern of Fe3O4 (not shown) confirmed the presence of only one phase, corresponding to magnetite with a lattice parameter a = 8.357 Å and a crystallite size of 16.6 ± 0.2 nm. The diffraction pattern of MGNC (not shown) confirmed the presence of a graphitic phase, in addition to the metal phase, suggesting that Fe3O4 nanoparticles were successfully encapsulated within a graphitic structure during the synthesis of MGNC. The core-shell structure of MGNC is unequivocally demonstrated in the TEM micrograph shown in Fig. 1b. Characterization of the MGNC textural and surface chemical properties revealed: (i) stability up to 400 oC under oxidizing atmosphere; (ii) 27.3 wt.% of ashes (corresponding to the mass fraction of Fe3O4); (iii) a micro-mesoporous structure with a fairly well developed specific surface area (SBET = 330 m2 g-1); and (iv) neutral character (pHPZC = 7.1). In addition, the magnetic nature of MGNC (Fig. 2) is an additional advantage for possible implementation of in situ magnetic separation systems for catalyst recovery.